Sensitivity of metal oxide gas sensors to non-parabolic intergranular barriers - Buono, Camila (2017)
We analyze the electrical conductivity of polycrystalline semiconductor solids due to the presence ofSchottky-type potential barriers formed at intergrains. The density of charged dopants along the grains isusually considered constant leading to parabolic intergranular potential barriers. If temperature is highenough to allow sufficiently mobility to the dopants, their resulting equilibrium distribution is far fromconstant leading to potential barriers that show a strong non-parabolic character. Implications for theelectrical conductivity and then on the sensitivity to barrier height and sample doping in metal oxide gassensors are discussed.